2019
DOI: 10.1080/14620316.2019.1574214
|View full text |Cite
|
Sign up to set email alerts
|

Vertical farming: a summary of approaches to growing skywards

Abstract: Pressure on agricultural land from a rising global population is necessitating the maximisation of food production per unit area of cultivation. Attention is increasingly turning to Vertical Farming (VF) approaches in an attempt to provide a greater crop yield per square meter of land. However, this term has been used to cover a broad range of approaches, from personal-or community-scale vegetable and herb growing to vast skyscrapers for commercial production of a wide range of crops. This article summarises t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
104
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 206 publications
(108 citation statements)
references
References 26 publications
0
104
0
4
Order By: Relevance
“…[ 54,55 ] This estimate does not take account of installation of agrivoltaics on soil‐less vertical/indoor farming, which promises to be one of the main solutions to avoid increasing the use of arable land and therefore limiting agriculture’s contribution to climate change. [ 56–58 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 54,55 ] This estimate does not take account of installation of agrivoltaics on soil‐less vertical/indoor farming, which promises to be one of the main solutions to avoid increasing the use of arable land and therefore limiting agriculture’s contribution to climate change. [ 56–58 ]…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the source of the electricity input was a determinant factor that, if carbon neutral (e.g., wind energy) could be optimised, it was found that vertical hydroponic production outperformed the two conventional types of agriculture (Romeo et al, 2018). More research to evaluate the environmental impacts, crop choice, economics and energy requirements of vertical farming in cities is needed (Beacham et al, 2019).…”
Section: Edible Urbanismmentioning
confidence: 99%
“…Approaches to vertical farming are numerous and varied, including green walls where produce is grown on a vertical or inclined surface and growth around vertically orientated cylinders. However, the most commonly used approach comprises stacked horizontal beds of soil‐based or soil‐free cultivation (Beacham, Vickers, & Monaghan, ). Vertical farming is a rapidly expanding industry (Kopf, ) that is receiving much interest and investment from a range of different parties and, perhaps due to its close links to urban agriculture, is lauded by some as the future of food production (Despommier, ).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence of the growth in vertical farming can be seen in countries such as Japan, currently the world leader in the sector (Kozai, ), where the number of farms has grown from 35 in 2009 to over 150 in 2017 (Hayashi, ). Despite their increasing use, vertical farming systems have received little in the way of rigorous scientific investigation to date (Al‐Chalabi, ; Beacham et al, ; Eigenbrod & Gruda, ; Mok et al, ; Pinstrup‐Andersen, ). Consequently, there are several important questions that remain to be addressed to help determine the viability of vertical farming for meaningful food production in the future.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation